Tree Species Biodiversity of a Sahelien Ecosystem in North-East Nigeria - Wakawa, Lucky; Suleıman, Aminu; Ibrahım, Yakubu; Adam, Lawan (Bartın Üniversitesi, 2017)
Trees species are crucial part of the ecosystem, they provides tangible and intangible benefits. The need for periodic assessment of these resources for management and conservation purposes is imperative. This study was therefore carried out to assess the tree species composition, diversity and richness of a Sahel ecosystem with the view of providing information for management and conservation purposes. The study area was stratified into three (3) from which transect of 1000 m was laid in each of the strata. 12 Sample plots of 40 m × 40 m in size were established in alternate position along each transect at 40 m interval. The height and diameter at breast height (dbh) of all living trees with dbh ?10.0 cm were measured and counted. The results from the study show that the study area has a total of 174 trees, 8 species and 14 Families. Margalef's index of species richness of 2.52, Pielou's species evenness index (EH) of 0.38, Shannon-Weiner index (H') of 1.97 and Simpson index of dominance (D) of 0.46 were recorded. The recorded biodiversity indices indicate a poor state of tree species, richness, composition and distribution within the environment.

Trees species are crucial part of the ecosystem, they provides tangible and intangible benefits. The need for periodic assessment of these resources for management and conservation purposes is imperative. This study was therefore carried out to assess the tree species composition, diversity and richness of a Sahel ecosystem with the view of providing information for management and conservation purposes. The study area was stratified into three (3) from which transect of 1000 m was laid in each of the strata. 12 Sample plots of 40 m × 40 m in size were established in alternate position along each transect at 40 m interval. The height and diameter at breast height (dbh) of all living trees with dbh ?10.0 cm were measured and counted. The results from the study show that the study area has a total of 174 trees, 8 species and 14 Families. Margalef's index of species richness of 2.52, Pielou's species evenness index (EH) of 0.38, Shannon-Weiner index (H') of 1.97 and Simpson index of dominance (D) of 0.46 were recorded. The recorded biodiversity indices indicate a poor state of tree species, richness, composition and distribution within the environment.
Tree Species Biodiversity of a Sahelien Ecosystem in North-East Nigeria